ANALISA PEMILIHAN METODE PETERSON DAN PEEK TERHADAP RUGI-RUGI DAYA AKIBAT KORONA PADA SUTET 275 KV PAYAKUMBUH - KILIRANJAO - Andrian Putra; Erhaneli Erhaneli (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2022)
The transmission line is a channel that connects the generating unit with the distribution unit in distributing electrical energy to consumers or loads with high voltage intermediaries of the type of overhead line. Transmission lines have criteria, namely short, medium and long channels. The longer the transmission line, the more cases that occur. One of them is found especially in air ducts in the form of corona events caused by weather conditions, cross-sectional area used, distance between beam conductors, surface conditions of conductors or insulators and system voltage. The purpose of this study was to see the effect of weather, cross-sectional area used, distance between beam conductors, surface conditions of conductors or insulators and system voltage on power losses and decreased efficiency caused by corona at SUTET 275 kV Payakumbuh - Kiliranjao with a line length of 126 ,4 km. Corona is characterized by the presence of a very visible purple (Violet) light that can be seen at night and causes power losses. Power losses caused by the corona in the Extra High Voltage Air Line (SUTET) must be taken into account, because at voltages above 100 kV the corona symptoms have started to get serious. Calculations were carried out using the Peterson equation based on technical data and power profile of the 275 kV Payakumbuh to Kiliranjao SUTET and temperature data. From the calculation it can be concluded that the power losses obtained from the Peterson equation with the same efficiency value (94.8 kW and 99 %). This is influenced by the temperature, which from August 2021 to July 2022 the temperature value is almost the same and results in the same destructive critical stress value.